Dynamic assessment in ESL writing with learning media based on augmented reality / Virgiawan Adi Kristianto, Harijadi Gunawan Buntoro Wahjono and Sri Handayani - Adi Kristianto, Virgiawan; Buntoro Wahjono, Harijadi Gunawan; Handayani, Sri (Faculty of Computer and Mathematical Sciences, 2021)
Augmented reality has experienced rapid development since the term was coined by Tom Caudell. This rapid development was made possible by the increasing development of mobile computing power and its functionality. Until finally, augmented reality is integrated on smart phones and makes this technology accessible to many parties. In education, augmented reality has designed learning tools to enrich the learning and teaching experience. This three-dimensional character can be used as a learning medium, especially in the field of English for Civil Engineering. This study uses a mixed methods approach, namely qualitative and quantitative. A qualitative approach with a case study design was used to determine student responses to the application of Augmented Reality learning media. This study followed the sandwich format on dynamic assessment which used pre and post – test so that a quantitative approach with a quasiexperimental research method and a non-equivalent control group design. Based on the results of the paired samples t test in the control and experimental groups, there is a significant difference between the mean between the control class and the experimental class.